Effects of Host Fruit and Larval Density on Development and Survival of Bactrocera sp. (Malaysian B). (Diptera: Tephritidae) - Tock Hing, Chua (1989)
The effects of five fruits (guava, mango, papaya, starfruit and tomato) on the larval survival, adult eclosion and size of Bactrocera sp. (Malaysia B) were investigated. The percentage pupation and adult emergence from pupae were not affected by different hosts, except for guava which gave the lowest percentage of adult emergence. Papaya and mango yielded the largest adult (>2mm head width). Comparison of composition of fruits indicates that a high percentage of carbohydrate and high pH in fruits would produce larger adults. High larval density reduced the percentage of larval survival, adult emergence and adult size.